INFLUENCE OF GLUTATHIONE SEED TREATMENT AND GAMMA IRRADIATION ON SEED GERMINATION OF REVALIDATED RICE VARIETY TELLAHAMSA UNDER AMBIENT STORAGE - K. JHANSI RANI, K. NAGESH, M. SREEDHAR, S. VANI SREE, RAZIA SULTANA and (The Journal of Research, PJTSAU, 2019)
Tellahamsa is a popular variety in Telangana state particularly during rabi season because of its cold tolerance ability. It possesses good seedling and vegetative stage cold tolerance with short duration and long slender grain having excellent cooking and good keeping quality. Hence, this variety has become very popular in semi urban and rural areas of Telangana, where it is grown every year on continuous basis. However, in view of non availability of short duration, cold tolerant, fine grain variety with good cooking attributes, the demand for this variety will stay for some more time in near future. In this connection, earlier research work indicated that this variety tends to lose viability drastically after storage of one to two cropping seasons.